2021
DOI: 10.7759/cureus.13357
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Oxygen Therapy Post COVID-19 Infection: Factors Leading to the Risk of Poor Outcome

Abstract: Background: Coronavirus disease 2019 (COVID-19) infection is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a single-stranded ribonucleic acid (RNA) β-coronavirus. Prolonged duration of symptoms, ill health, disability, and need for hospitalisation are all well-known features of severe COVID-19 disease. Objective: To describe the epidemiological, clinical and imaging characteristics of hospitalised patients of COVID-19 who required prolonged oxygen therapy after testing negative for SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
0
10
1
1
Order By: Relevance
“…Tis is in contrast with a study from India by Ray et al [9] that showed the mean duration of oxygen administration was 4.6 ± 1.7 days in the subgroup in which complete weaning from oxygen therapy was possible. However, in the same study [9], the in-hospital oxygen requirement among the patient group in which weaning of oxygen was not possible was 6.0 ± 3.1 days. Tese diferences could be due to the larger sample size in this study compared to ours.…”
Section: Discussioncontrasting
confidence: 74%
“…Tis is in contrast with a study from India by Ray et al [9] that showed the mean duration of oxygen administration was 4.6 ± 1.7 days in the subgroup in which complete weaning from oxygen therapy was possible. However, in the same study [9], the in-hospital oxygen requirement among the patient group in which weaning of oxygen was not possible was 6.0 ± 3.1 days. Tese diferences could be due to the larger sample size in this study compared to ours.…”
Section: Discussioncontrasting
confidence: 74%
“…[ 13 ] Elderly male patients of COVID-19 with coronary artery disease having multiple comorbidities are at a high risk of mortality. [ 14 ] In the absence of comorbidities, the mortality was <5% until the age of 80 years. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Ray et al, our study findings also showed patients with uncontrolled diabetes mellitus and other co-morbidities at an increased risk of prolonged hospitalization and oxygen therapy when infected with COVID-19. Elderly male patients with multiple co-morbidities show an especially high risk of mortality following COVID infection [ 30 ]. One could therefore expect high levels of HbA1C to predict a more severe course in patients with COVID-19.…”
Section: Discussionmentioning
confidence: 99%